2004
DOI: 10.1110/ps.03550404
|View full text |Cite
|
Sign up to set email alerts
|

Proteins can convert to β‐sheet in single crystals

Abstract: Raman microscopy was used to follow conformational changes in single protein crystals. Crystals of native insulin and of the 5S and 12S subunits of the enzyme transcarboxylase showed a mixture of Raman marker bands signifying ␣-helix, ␤-sheet and nonordered secondary structure. However, by reducing the S-S bonds in the insulin crystal, or by lowering the pH for the 5S crystal, or by soaking substrates into the 12S crystal, the secondary structure in each crystal became predominantly ␤-sheet. The ␤-form crystal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
70
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(73 citation statements)
references
References 28 publications
3
70
0
Order By: Relevance
“…For example, a massive conversion from˛-helix toˇ-strand was observed in insulin crystals on reduction and in transcarboxylase assemblies on acidification. 50 Hence Raman crystallography nicely complements x-ray diffraction where the latter fails.…”
Section: Large Conformational Changes In Single Crystals Of Proteinsmentioning
confidence: 97%
See 1 more Smart Citation
“…For example, a massive conversion from˛-helix toˇ-strand was observed in insulin crystals on reduction and in transcarboxylase assemblies on acidification. 50 Hence Raman crystallography nicely complements x-ray diffraction where the latter fails.…”
Section: Large Conformational Changes In Single Crystals Of Proteinsmentioning
confidence: 97%
“…49 Using oriented samples of model˛-helical proteins, the authors also demonstrated the utility of the 1340 cm 1 band in determinations of˛-helix orientations by polarized Raman microspectroscopy. 49 In addition, a Raman band at ¾935-940 cm 1 has been correlated with the amount of˛-helical structure 47,50 and was tentatively assigned to the N-C˛-C skeletal mode of the polypeptide backbone. 48 Detailed normal-mode analyses of˛-helical polyalanine showed that this vibration belongs to E 2 symmetry and contains contributions from CH 3 rocking, C-N and N-C˛stretchings and C-N-C˛deformation.…”
Section: Novel Empirical Backbone Assignments and Interpretationsmentioning
confidence: 99%
“…(collagen); random coil (collagen, elastin), [23,38] ß-pleated sheet motion [39,40] 1659, 1670 1616 1612, 1617, 1625 C-C structure: Tyr, Trp [44] 1604 (very weak) 1604 C-C in-plane bend: Phe, Tyr [44] 1582 1579 Ring structure: G, A [20,44] [20,30,37] …”
mentioning
confidence: 99%
“…Unfortunately, upon chemical reduction crystals do not diffract anymore, and no crystallographic counterpart is available. An analogous conformational transition occurred upon pH decrease of 5S subunit of transcarboxylate (Zheng et al, 2004), where modifications in the Amide III region (Mikhonin et al, 2006) suggested a significant modification into the crystal matrixes. Also hydration can affect deeply Amide I, and eventually secondary structure, as observed for a collagen-like polypeptide, for which Raman spectrum of the lyophilized powder showed very different Amide I frequencies when compared to single crystals (Figure 3, from Merlino at al., 2008a).…”
Section: Raman Detection Of Chemical Modifications Perturbing Secondamentioning
confidence: 91%
“…By taking advantage from the sensitivity of Amide I band to conformational variations, Thomas revealed a β-sheet to α-helix transition upon TCEP [tris(2-carboxyethyl)phosphine] addition to bovine insulin crystals (Zheng et al, 2004). Unfortunately, upon chemical reduction crystals do not diffract anymore, and no crystallographic counterpart is available.…”
Section: Raman Detection Of Chemical Modifications Perturbing Secondamentioning
confidence: 99%